Investigating the thin film growth of [Ni(Hvanox)2] by microscopic and spectroscopic techniques - Sapre, Atharva U; Vlček, Jan; de Prado, Esther; Fekete, Ladislav; Klementová, Mariana; Vondráček, Martin; Svora, Petr; Cuza, Emmelyne; Morgan, Grace G; Honolka, Jan; Kühne, Irina A (Nanoscale advances, 2025)
We have investigated [Ni(Hvanox)2] (H2vanox = o-vanillinoxime), a square-planar Ni(ii) complex, for the preparation of thin films using organic molecule evaporation. Low pressure experiments to prepare thin films were conducted at temperatures between 120-150 °C and thin films of increasing thicknesses [Ni(Hvanox)2] (16-336 nm) have been prepared on various substrates and been analyzed by microscopic and spectroscopic methods. Scanning electron microscopy (SEM), atomic force microscopy (AFM) and transmission electron microscopy (TEM) were used to reveal a rough surface morphology which exhibits a dense arrangement of elongated, rod and needle-like nanocrystals with random orientations. It also enabled us to follow the growth of the thin films by increasing thickness revealing the formation of a seeding layer. X-ray photoelectron spectroscopy (XPS and 3D ED), TEM and X-ray diffraction (XRD) were utilized to confirm the atomic structure and the elemental composition of the thin films.